Memórias, deslocamentos, lutas e experiências de um exilado espanhol: Pedro Brillas (1919-2006) - Tomanik, Geny Brillas (2017)
This thesis aims to analyze and discuss the life trajectory, including the recurring displacements, of Pedro Brillas (1919-2006), born in Barcelona, anarchist and former fighter that, when he was 17 years old, voluntarily enlisted the republican anti-Franco forces in the Spanish Civil War (1936-1939), where he was wounded. At the end, when the defeat was imminent – motivated by the advance and the attack of the Franco army, with the support or the Nazi Condor Legion –, the young man participated of the Spanish flow towards France denominated La Retirada. This massive Spanish exodus and the republican exile were consequences of the Spanish Civil War. When crossing the French border, in February 1939, he became a permanent exile, with only 19 years old. The guiding thread and the documentary body of the research is based on the private archive of Pedro Brillas, an historical agent, composed of several memoirs, journals (some of them from the war front), letters, official letters, personal documents (between wars) and pictures. This proposal is justified because it is a great and unprecedented archive that reveals common and extraordinary experiences, subjectivities, and narrates the displacements of Spanish exiles, as lived collectively. These e/immigrant‟s materials usually housed in chests and drawers, enables to retrieve and update the individual and collective memory, representing a great documental treasure of popular production, often invisible – and almost unavailable in archives records –, have gained value in the contemporary historiographic research. The memoirist witnessed, lived and recorded several historic facts and dramatic experiences, such as the Spanish Civil War, the Second World War (lived in France and Germany), the life at the French concentration camps, survived dangers, insecurities and uncertainty. Also, lived the quotidian of the war and the after-war period, in Germany, France and later in Brazil, to where he immigrated in 1951 with his family, supported by the International Refugee Organization (IRO), and was finally able to establish. The research is articulated with the historiographical studies about the Spanish Civil War and the international displacements of Spanish, particularly regarding the refugees and politic exiles, as well as the reception in these countries; and with studies on memory and identity